Pengaruh Playful Work Design terhadap Work Engagement pada Dosen - Bima Satria Nugraha; Hendro Prakoso (UNISBA Press, 2023)
Abstract. The purpose of this study was to determine how much influence the playful work design has on work engagement in lecturers. This research method is quantitative with a causality research design. The sample in this study was 95 lecturers from Bandung Islamic University, Indonesian Education University, and Pasundan University. The measuring instrument used is the Playful Work Design Scale developed by Scharp Bakker et al (2021) and the Utrecht Work Engagement Scale-17 (UWES- 17) from Schaufeli & Bakker (2002) adapted by Sutisna et al (2020). The results of the study show that playful work design has a major influence on work engagement by 60.4% with the aspect that provides the greatest contribution, namely designing competition on work engagement in the participants of this study. Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui seberapa besar pengaruh dari playful work design terhadap work engagement pada Dosen. Metode penelitian ini adalah kuantitatif dengan desain penelitian kausalitas. Jumlah sampel pada penelitian ini adalah 95 dosen yang berasal dari Universitas Islam Bandung, Universitas Pendidikan Indonesia, Universitas Pasundan. Alat ukur yang digunakan yaitu Playful Work Design Scale yang dikembangkan oleh Scharp Bakker et al (2021) dan Utrecht Work Engagement Scale-17 (UWES-17) dari Schaufeli & Bakker (2002) yang diadaptasi oleh Sutisna et al (2020). Hasil penelitian menunjukan bahwa playful work design memberikan pengaruh besar terhadap work engagement sebesar 60,4% dengan aspek yang memberikan kontribusi paling besar yaitu designing competition terhadap work engagement pada partisipan dosen penelitian ini.